Gestão de centros históricos: uma avaliação da política de requalificação urbana de Natal/RN - Souza, Daline Maria de (2013)
From the second half of the century XX, in many Brazilian cities, the "historic centers" stop being the most densely populated areas of the city, accumulate degradation of the built environment and its functions have physical, social and economic resignified when also intensified interventions in these same centers Historic focused its redevelopment. This work aims to reflect on the experience of urban regeneration in the historic center of Natal, addressing the strategies adopted in the implementation of public policies and how these improve the effectiveness of actions, processes and outcomes for which turn the management of the historic center in question. In Natal, is identified in the neighborhoods of the Upper Town and Ribeira, the historic city center, a large distortion of their ancient architectural complex, the use of sub-urban infrastructure and emptying in the evenings and weekends. Shares redevelopment of the historic center of Natal are considered late, it is only recently that these neighborhoods were objects of policies and projects generally aimed at enhancing the cultural attraction of the area, and not always, it can be said that they have relevance in development process of the city. Added to this, there is the slowness of the interventions, although the zoning as an area of historic preservation has been done for over two decade. In Natal, the ideas of sustainable development articulated a proposed redevelopment of its historic center is still far from being achieved, but on the other hand, the latest phase of implementation of plans and projects in the area, indicating the intention to transform practical experience in the formulations and proposals in relation to these ideals